Perception about textbooks in math teaching-learning of Mathematics - Montaluisa-Vivas, Ángel (2021)
Textbooks are a necessary resource in the science teaching-learning process and should consider, among others, the curricular elements: learning objectives, mathematical content and evaluation. The purpose of this research is to determine the level of satisfaction that the development of these elements generates in students and teachers, expressed in these textbooks used in the Ecuadorian educational system. It should be noted that the Ministry of Education provides this school material free of charge to all public institutions in the country and, therefore, motivates research on its application and use. This study has a quantitative approach and is exploratory and descriptive, so an observation instrument was used for data collection. The results are expressed by levels of schooling of both the General Basic Education sub-level and the General Unified Baccalaureate and by the curricular elements studied. Finally, it was concluded that the objectives proposed for the Unified General Baccalaureate have a higher level of satisfaction than those declared for General Basic Education. It was also concluded for both levels that there is a medium level of satisfaction with the elements investigated in the textbooks, which means that the students who use them are not oriented to continue with more complex learning.